The Risk Assessment for a Single Building on the Landslide Areas and Floodplains = Ocena ryzyka dla obiektu budowlanego na terenie osuwiskowym i zalewowym - Kokoszka, Wanda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Mass movements and floods are natural hazards posing a threat to the environment and bring significant economic losses. The flooding and landslide are risks in the municipalities of south-eastern Poland. Long-lasting rains cause initialize process of landslides on the slopes above the river valley, as well as flooding of local infrastructures (buildings, roads, railway tracks) located near water courses.
Keywords: landslide; geotechnical parameters; floodplains; risk assessment; osuwisko; parametry geotechniczne; tereny zalewowe; ocena ryzyka